Comparative technical analysis of lipoaspirate mechanical processing devices. (11th August 2020) - Veronese, Sheila; Dai Prè, Elena; Conti, Giamaica; Busato, Alice; Mannucci, Silvia; Sbarbati, Andrea
Abstract: Fat grafting is a well‐established procedure in reconstructive, aesthetic, and regenerative medicine, in particular due to the presence in the adipose tissue of a high concentration of mesenchymal stem cells. The need to reduce fat processing times, for an immediate clinical use and regulatory restrictions on the degree of manipulation of human tissues, has led to the development of numerous devices for the mechanical, nonenzymatic processing of adipose tissue. The aim of this study is to describe the state of the art of mechanical devices used for fat processing, performing a technical analysis of the currently commercially available devices. This should facilitate the development of new devices that improve therapeutic results.